2017
DOI: 10.18203/2349-2902.isj20175903
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, clinical manifestations and outcome of TUR (transurethral resection) syndrome in patients undergoing TURP under spinal anaesthesia: results from clinical observations in a cohort of 50 patients at a tertiary care centre in North India

Abstract: Background: ‘TUR syndrome’ is clinically detectable in 2% of patients undergoing an otherwise safe operation. Currently, spinal anaesthesia is the most widely anaesthetic technique for TURP as it is easier to detect signs of TUR syndrome in an awake patient. This study aimed at looking at the clinical spectrum and outcomes of TUR syndrome in patients undergoing TURP under spinal anaesthesia.Methods: This clinical study was conducted over a period of 6 months in the departments of anesthesiology and urology at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
2
1
0
Order By: Relevance
“…Additionally 7(10.6%) had transient incontinence on catheter removal, which on follow up visits they all got better, this may be because of the oedema of the sphincter post TURP which explains its disappearance as the oedema subsides. This is similar to findings by other studies [17,29] A total of 16 (6.4%) of the participants needed blood transfusion, this was higher almost approaching that of open prostatectomy. Most 13(82.3%) of those who needed blood had prostate >80grams.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally 7(10.6%) had transient incontinence on catheter removal, which on follow up visits they all got better, this may be because of the oedema of the sphincter post TURP which explains its disappearance as the oedema subsides. This is similar to findings by other studies [17,29] A total of 16 (6.4%) of the participants needed blood transfusion, this was higher almost approaching that of open prostatectomy. Most 13(82.3%) of those who needed blood had prostate >80grams.…”
Section: Discussionsupporting
confidence: 92%
“…Although this procedure is a gold standard for management of BPH, it is associated with other complications other than TUR syndrome which occurs in up to 10% of patients [17]. These includes Bleeding requiring blood transfusion, capsular perforation, total incontinence, failure to void (18) and perioperative deaths [19].…”
Section: Introductionmentioning
confidence: 99%
“…None of the patients in the index study had TUR syndrome similar to what was found by earlier studies [15], [23]. This, however, is at variance with the 10% and 23.5%incidence rates of TUR syndrome documented by George et al [24] in India and Nakahira et al [22] in Japan. Incidence rates of 2%, 3.2% and 4.8% were documented by Persu et al [17] in Romania, McGowan-Smyth et al [25] in the United Kingdom and Chukwujama et al [19] in Nigeria, respectively.…”
Section: Discussionsupporting
confidence: 63%